The Resolution of Tidal Constituents - Godin, Gabriel (The International Hydrographic Review, 2015)
The effect of the background noise on the analyzed values of the tidal constituents can be evaluated if it is assumed to be of purely random character. The noise effectively prohibits the resolution of very close constituents while its influence is virtually negligible on well separated constituents. In the latter instance, the interference of the unanalyzable constituents becomes the major source of errors in short analyses.